Corona virus myocarditis in pediatric age group: a rare manifestation of pandemic - U., Praveen; Jhadav, Datta; Thakare, Jitesh M.; G., Reshmi; Krishnan, Priyanka (International Journal of Contemporary Pediatrics, 2021)
Myocarditis is an uncommon disease of adult and pediatric age group, characterized by inflammatory cell infiltrates, myocyte necrosis, or myocyte degeneration due to a myriad of causes and resulting in variable degrees of myocardial dysfunction. Which may be caused by infections, connective tissue disorders, granulomatous diseases, toxic agents or can be idiopathic. Viral infections are the most common etiology accounting for more than 50-60% of cases, particularly enterovirus (Coxsackie virus) and adenovirus groups. The disease is typically sporadic but may be epidemic. Manifestations of myocarditis range from asymptomatic or nonspecific generalized illness to acute cardiogenic shock and sudden death. In our case 10-year-old boy presented with history of fever and cough of 2 days duration. On examination patient found to be having tachycardia and tachypnea without other signs of heart failure. chest x-ray suggestive of bilateral pneumonia, ECG showed features of Myocarditis without any echocardiographic or cardiac enzyme abnormality. Child tested positive for corona virus rapid antigen test. Started on Favipiravir, corticosteroids and managed symptomatically. Child’s heart rate normalized over a period of 4 days. Patient subsequently discharged with the advice of follow up echocardiography.